Visible light-induced photochemical oxygen evolution from water by 3, 4, 9, 10-perylenetetracarboxylic dianhydride nanorods as an n-type organic semiconductor. Issue 3 (14th December 2015) - Li, Jia-Xin; Li, Zhi-Jun; Ye, Chen; Li, Xu-Bing; Zhan, Fei; Fan, Xiang-Bing; Li, Jian; Chen, Bin; Tao, Ye; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : The designed nanorods with cobalt oxide achieve an AQE of 4.6 ± 0.3% for oxygen evolution under visible light irradiation at 410 nm. Abstract : 3, 4, 9, 10-Perylenetetracarboxylic dianhydride (PTCDA) nanorods as an n-type organic semiconductor are utilized to construct a powder-based photocatalytic water oxidation system with cobalt oxide as a cocatalyst, which achieved an apparent quantum efficiency of 4.6 ± 0.3% under visible light irradiation at 410 nm.